Pelayanan pengujian kekuatan pipa HDPE di Laboratorium Kimia Material Departemen Teknik Material dan Metalurgi FTIRS-ITS - Rohmannudin, Tubagus Noor; Sulistijono, Sulistijono; Amrulloh, M. Farian; Nafi’, Dian; Fachri, Muhammad (Penamas: Journal of Community Service, 2024)
HDPE pipes are widely used in various industries, such as drinking water and sewage infrastructure, petroleum, agriculture, and construction. The advantages of HDPE pipes include corrosion resistance, light weight, easy installation, and low maintenance costs. Checking the quality of HDPE pipes, spesifically from industry that we tested, is important to ensure infrastructure safety, prevent system failure, improve operational efficiency, obtain user satisfaction, and conserve resources. We evaluated HDPE pipes with type PN 12.5 SDR 13.6 from industry in terms of resistance to hydrostatic pressure, tensile strength, and expansion capability. The evaluation was carried out at the Material Chemistry Laboratory of the Department of Material Engineering and Metallurgy FTIRS-ITS ITS in accordance with the standards of SNI 4829.2: 2015, ASTM D 638 M, and SNI 2553: 1999. The results show that HDPE pipes can withstand hydrostatic pressure up to 12 bar without leakage. The average tensile strength is 43.34 MPa with an average elongation of 354%, indicating ductile pipe properties with necking. Pipe expansion was observed to be 0.195%, indicating a good ability of the pipe to undergo expansion.